IMPLEMENTASI DECISION SUPPORT SYSTEM METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE DALAM PEMILIHAN RUMAH KOST DISEKITAR KAMPUS UNIVERSITAS NEGERI MEDAN - Ronaldo Mardianson Sinaga; Fahri Aulia Alfarisi Harahap; Anggi Tasari; Deby Yandra Niska (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
The need for information on the boarding house and its location at this time is very important. However, due to the large amount of information about boarding houses and their available locations, the general public, especially students studying at universities, are confused about finding the location of a boarding house that suits their needs. Nowadays, many people use websites to find information about boarding houses, but the website only provides or provides information. Therefore, this research was built with the title "Implementation of the Decision Support System Method of Simple Multi Attribute Rating Technique in the Selection of Boarding Houses Around the Medan State University Campus" which aims to create a website-based information system in determining boarding recommendations so that the general public, especially students, can choose boarding houses. - boarding according to their criteria and needs. The method used in this research is the Simple Multi Attribute Rating Technique (SMART).